2015
DOI: 10.3384/diss.diva-118291
|View full text |Cite
|
Sign up to set email alerts
|

Radiation properties of coil-coated steel in building envelope surfaces and the influence on building thermal performance

Abstract: Recent studies have shown that the optical properties of building exterior surfaces are important in terms of energy use and thermal comfort. While the majority of the studies are related to exterior surfaces, the radiation properties of interior surfaces are less thoroughly investigated. Development in the coil-coating industries has now made it possible to allocate different optical properties for both exterior and interior surfaces of steel-clad buildings. The aim of this thesis is to investigate the influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Further description of the surface materials and the experimental method have been described. 5,17 Air and surface temperatures were measured at 14 positions totally according to Figure 1. Each test cabin was equipped with one PC-logger with the cold junction accuracy of AE0.5 C at 25 AE 10 C and the voltage accuracy of AE0.01%.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further description of the surface materials and the experimental method have been described. 5,17 Air and surface temperatures were measured at 14 positions totally according to Figure 1. Each test cabin was equipped with one PC-logger with the cold junction accuracy of AE0.5 C at 25 AE 10 C and the voltage accuracy of AE0.01%.…”
Section: Measurementsmentioning
confidence: 99%
“…The density correlation was based on the incompressible ideal gas assumption. The RNG k-" constants used in this numerical calculation have been described 17 together with the corresponding equations. The meshed computational domain, including the building envelope with homogenous properties, as well as the indoor air volume was constructed using the ANSYS/Icepak (version 14.5).…”
Section: Cfd Simulationmentioning
confidence: 99%
“…Joudi 14 studied the radiation properties of the surface, including the emissivity coefficient of interior surfaces, modeling methods, and its results on building energy performance and the thermal environment of buildings. This study indicated that surface with low emissivity can increase indoor air temperature vertical gradient, which is dependent on the time of day and outside weather conditions.…”
Section: Introductionmentioning
confidence: 99%